Vegetarian substitutes for meat in traditional recipes as sources of group B vitamins - Flores, Cristina (2020)
The increasing number of vegetarians in Portugal in the last decade has led to a growing demand of ingredients that can replace meat in the traditional recipes that are part of Portuguese gastronomic culture. Even though those ingredients are mainly, selected for their protein content often, the similarity of their texture to meat is the primary choosing criterion. Objective: Our purpose with this work was to evaluate some of these ingredients as sources of four group B vitamins: B1 (thiamin), B2 (riboflavin), B3 (niacin) and B6 (pyridoxine). Methodology: Data for vitamin content of 10 ingredients: seitan, jackfruit, edamame, tempeh, tofu, coconut, eggplant, beetroot, cauliflower and mushrooms, was obtained from several of the food composition tables included in EuroFIR databases list. The mean value for each vitamin was calculated for each ingredient and compared with the Daily Reference Intake (DRI) for adults, in terms of percentage. Main findings: Relevant contents of vitamins, equal or higher than 15% of the DRI (14), were reported for five of the ingredients: B6 in jackfruit, B1 and B2 in edamame, B2 and B6 in tempeh, B6 in beetroot and B2 and B3 in mushrooms. With the exception of seitan, for which vitamin content is reported as null, and eggplant, 100 g of each of the other ingredients can contribute to the intake of 10% of the DRI of, at least, one of the vitamins in study. Conclusion: Most of the meat substitutes evaluated are good choices in terms of group B vitamins content.